East Germany Yesterday and Tomorrow - Dalia Marin (Wirtschaftsdienst)
Abstract In November 2019, Germany celebrated 30 years since the fall of the Berlin Wall. But the mood today is gloomy. Two-thirds of East Germans consider themselves second-class citizens, according to a survey by the Allensbach Institute for Public Opinion Research. The process of convergence between eastern and western Germany has come to a standstill and seems to be reversing. East Germans today vote differently, think differently and feel differently. Germany is a country with two souls.